FACTORS AFFECTING AUTO INSURANCE IN INDIA (International Journal of Engineering Sciences & Management Research, 2016)
Auto Insurance in India deals with the insurance covers for the loss or damage caused to the automobile or its parts due to natural and man-made calamities. It provides accident cover for individual owners of the vehicle while driving and also for passengers and third party legal liability. There are certain general insurance companies who also offer online insurance service for the vehicle. Major contribution of growth of General insurance industry in India has come from Auto insurance sector. It alone accounts for around 53% of total general insurance premium income in India. The paper provides an understanding on factors affecting growth of Auto insurance in India. Four major factors like Motor vehicle sales, Number of Road accidents, Road length and Auto claims incurred affecting growth of Auto insurance premium are being studied. Statistical tools used for the study is Multiple Regression analysis. This industry is prone to accidental claims and its bottom line is always under tremendous pressure. In recent times Insurance Regulatory and Development Authority (IRDA) has taken bold step by increasing the premium rate of third party liability. From 1st April 2015 IRDA has almost doubled third party motor insurance premium of all categories of vehicles. This will help in profitable and meaningful growth on Auto insurance sector.